A new 500 kb haplotype associated with high CD8+ T-lymphocyte numbers predicts a less severe expression of hereditary hemochromatosis - Mascarenhas Cláudia; Krikler Samuel H; Whittington Chris; Cruz Eugénia; Lacerda Rosa; Vieira Jorge; Porto Graça (BMC, 2008)
Abstract Background Hereditary Hemochromatosis(HH) is a common genetic disorder of iron overload where the large majority of patients are homozygous for one ancestral mutation in the HFE gene. In spite of this remarkable genetic homogeneity, the condition is clinically heterogeneous, varying from a severe disease to an asymptomatic phenotype with only abnormal biochemical parameters. The recent recognition of the variable penetrance of the HH mutation in different large population studies demands the need to search for new modifiers of its phenotypic expression. The present study follows previous observations that MHC class-I linked genetic markers, associated with the setting of CD8+ T-lymphocyte numbers, could be clinically relevant modifiers of the phenotypic expression in HH, and aimed to find new markers that could be used as more reliable prognostic variables. Methods Haplotype analysis, including seven genetic markers within a 1 Mb region around the microsatellite D6S105 was performed in a group of 56 previously characterized C282Y homozygous Portuguese patients. Parameters analyzed in this study were total body iron stores, clinical manifestations related with HH and immunological parameters (total lymphocyte numbers, CD4+ and CD8+ T-lymphocyte numbers). An independent group of 10 C282Y homozygous patients from Vancouver, Canada, were also included in this study and analyzed for the same parameters. Results A highly conserved ancestral haplotype defined by the SNP markers PGBD1-A, ZNF193-A, ZNF165-T (designated as A-A-T) was found associated with both abnormally low CD8+ T-lymphocyte numbers and the development of a severe clinical expression of HH. In a small proportion of patients, another conserved haplotype defined by the SNP markers PGBD1-G, ZNF193-G, ZNF165-G (designated as G-G-G) was found associated with high CD8+ T-lymphocyte numbers and a milder clinical expression. Remarkably, the two conserved haplotypes defined in Portuguese patients were also observed in the geographically different population of Canadian patients, also predicting CD8+ T-lymphocyte numbers and the severity of disease. Conclusion These results may have important implications not only for approaching the question of the penetrance of the hemochromatosis gene in different world populations but also to further narrow the region of interest to find a candidate gene involved in the setting of CD8+ T-lymphocyte numbers in humans.